Polysaccharide-based self-healing polymer binder via Schiff base chemistry for high-performance silicon anodes in lithium-ion batteries. (10th July 2021) - Rajeev, K.K.; Nam, Jaebin; Jang, Wonseok; Kim, Yeonho; Kim, Tae-Hyun
Abstract: The use of crosslinked glycol chitosan (GCS) is explored as an efficient, low-cost, eco-friendly, and water-soluble polymer binder for Si anodes in lithium-ion batteries (LIBs). A supramolecular, self-healing 3D network is constructed between the amino groups in glycol chitosan and the dialdehyde groups of oxidized alginate (OSA) through dynamic Schiff base reactions. The oxidized alginate crosslinker spontaneously reacts with the natural polymer to form an imine bond, which leads to the formation of a supramolecular network. This mechanism provides this polymer binder with strong and dynamic covalent bonding for Si anodes (GCS- I -OSA), which can effectively buffer the large volume changes in Si that occur during the lithiation/delithiation process. The obtained GCS- I -OSA-10 binder-based Si anode exhibited excellent electrochemical performance, with a high degree of reversibility (2316 mAh g −1 at 0.2 C after 100 cycles). In addition, the GCS- I -OSA-10 electrode exhibited excellent rate performance, achieving high reversibility (2185 mAh g −1 at a high current density of 5C) and high long-term cycling stability (1507 mAh g −1 after 200 cycles), even at a high current density (1C). Moreover, even when applied to commercial Si/graphite composite anodes, this GCS- I -OSA-10 binder was able to deliver superior cycle performance (with a specific capacity of 1364 mAh g −1 at a current density of 0.2 C after 100 cycles), demonstrating excellent potential for practical applications in LIBs. Graphical abstract: Image, graphical abstract